If it's not what You are looking for type in the equation solver your own equation and let us solve it.
6.6=2.3+y
We move all terms to the left:
6.6-(2.3+y)=0
We add all the numbers together, and all the variables
-(y+2.3)+6.6=0
We get rid of parentheses
-y-2.3+6.6=0
We add all the numbers together, and all the variables
-1y+4.3=0
We move all terms containing y to the left, all other terms to the right
-y=-4.3
y=-4.3/-1
y=4+0.3/1
| 15y+20=12y+50 | | 2-2x=x-38 | | 5x=30+8x | | 4/t=3/t+5 | | 4x+550=3x+700 | | |4k-2|=2 | | 5x+8=x-7+7x | | 18x+20=3x+80 | | -2x+12=-2(-4x+7) | | 8a^2-a+2=0 | | 2x+(3x-6)=78 | | 8x+16=192 | | 70x=60x+30 | | 2=13-2x | | .35+.3x=45+2x | | u-59=109 | | j-47=6 | | 0.2x-1.3=5.1 | | 4x-20-7=3 | | 1.1x+2.8=6.1 | | 3/5y+16=10 | | -9(z-6)=-4(z+4) | | 1=10^x | | 5(x+3)-2(x-6)=6(x+3) | | 9x^2=12x+4 | | -6(r+6)=+5(r-4) | | e=12.2=40 | | 1n+5n+7=43 | | 5(2x-3)=2(4x+3)-10 | | 5x+67=1 | | 0.3^x=0.012 | | 1/2(3x+6)(x+4)=72 |